Associations of blood lead, cadmium, and mercury with resistant hypertension among adults in NHANES, 1999-2018 - Hao Chen; Yunfeng Zou; Xuebing Leng; Feng Huang; Rongjie Huang; Akemi Wijayabahu; Xinguang Chen; Yunan Xu (Komiyama Printing Co. Ltd, 2023)
Background: Resistant hypertension (RHTN), a clinically complex condition with profound health implications, necessitates considerable time and allocation of medical resources for effective management. Unraveling the environmental risk factors associated with RHTN may shed light on future interventional targets aimed at reducing its incidence. Exposure to heavy metal has been linked to an increased risk of hypertension, while the relationship with RHTN remains poorly understood. Methods: Using the 1999-2018 National Health and Nutrition Examination Survey (NHANES) data, we examined the association of blood lead (Pb), cadmium (Cd), and mercury (Hg) with RHTN using a multinomial logistic regression model. The combined effects of the metals and the contribution of each metal were assessed using a weighted quantile sum (WQS) analysis. Results: A total of 38281 participants were included in the analysis. Compared with no resistant hypertension (NRHTN), per 1 µg/dL increase in blood Pb concentration, the proportion of RHTN increased by 16% [adjusted odds ratio (aOR), 1.16; 95% confidence interval (CI) 1.01-1.32]. When analyzed by quartiles (Q), the aOR [95% CI] for Pd was 1.30[1.01,1.67] (Q4 vs. Q1); there was a significant dose-response relationship (p < 0.05). Likewise, as a continuous variable, each 1 µg/dL increase in blood Cd level was associated with a 13% increase in the proportion of RHTN (aOR: 1.13; 95%CI: [1.00,1.27]); when analyzed as quartile, aOR [95% CI] for Cd were 1.30[1.01,1.69] (Q3 vs. Q1), and 1.35[1.03,1.75] (Q4 vs. Q1); the dose-response relationship was significant (p < 0.05). WQS analysis showed a significant combined effects of Pb, Cd, and Hg on RHTN, with Pb as the highest weight (0.64), followed by Cd (0.25) and Hg (0.11). Stratified analysis indicated that the associations for the two heavy metals were significant for participants who were male, ≼60 years old, and with kidney dysfunction. Conclusion: Findings of this study with national data provide new evidence regarding the role of environmental heavy metal exposure in RHTN. The prevention strategies aimed at reducing heavy metal exposure should particularly focus on Americans who are middle-aged, male, and afflicted with kidney dysfunction.